Factors associated with job strain and job dissatisfaction among research laboratory staff of a Malaysian public university - Fadaei, Nehzat (2014)
One of the most common and costly health problems at the work environment is job stress. Job strain or job stress is widely studied among various occupations. However, not many studies on job strain and job dissatisfaction have been done among research laboratory staff in Malaysia. A cross-sectional study was conducted among research laboratory staff in 9 faculties and 8 institutes of University Putra Malaysia. The objectives are to determine the prevalence of job strain and job dissatisfaction, and also to ascertain the association between job strain,job dissatisfaction, socio-demographic and occupational factors among laboratory staff of UPM. Probability appropriate to size sampling and simple random sampling method was used and data were collected via Job Content Questionnaire (JCQ) from September 2012 to February 2013. The estimated sample size for this study was 312 laboratory staff. A total of 285 laboratory staff with at least one year job tenure participated in this study. The finding revealed that 20.7% of research laboratory staff had high job strain and 47% of them reported job dissatisfaction. Four factors were found to be significantly associated with job strain; gender (χ2 =4.996, df= 1, p= 0.025), educational level (χ2 =4.861, df= 1, p= 0.027), created skill (χ2 =17.156, df= 1, p= 0.001), physical exertion (χ2 =8.988, df= 1, p= 0.003). Four factors were significantly associated with job dissatisfaction; age (χ2 =10.140, df= 1, p= 0.001), social support(χ2 =5.494, df= 1, p= 0.019), hazardous conditions(χ2 =11.451, df= 1, p= 0.001), toxic exposures(χ2 =14.617, df= 1, p= 0.001). Logistic regression analysis indicated that male laboratory staffs were two times more likely to complain of job strain (adjusted OR= 2.130, 95% CI: 1.106-4.101, p= 0.024). Laboratory staffs with lower created skill are 4 times more likely to experience job strain (adjusted OR= 3.572, 95% CI: 1.746-7.310, p= 0.001); however, research laboratory staff with higher physical exertion were 3 times more likely to complain of high job strain (adjusted OR= 2.696, 95% CI: 1.216-5.979, p= 0.015). Furthermore, laboratory staffs with age 35, and less had 2 times more job dissatisfaction than the older staff (adjusted OR= 2.108, 95% CI: 1.241- 3.582, p= 0.006). Laboratory staffs with higher toxic exposures 2 times more dissatisfied of their job (adjusted OR= 1.887, 95% CI: 1.062-3.353, p= 0.030). Created skill is the most important factor associated with high job strain among research laboratory staffs. Meanwhile, the most significant factor in related with job dissatisfaction is age. Therefore, emphasis on training the research laboratory staff and encouraging them to increase their skill level would be effective to reduce high job strain. The management should have the training plans to increase the knowledge on toxic exposures among younger laboratory staff to reduce job dissatisfaction among them.